Interação genótipo x ambiente, adaptabilidade e estabilidade de híbridos de MELÃO pele de sapo via modelo misto - Silva, Edicleide Macedo da (Universidade Federal Rural do Semi-Árido, 2017)
This study aimed to carry out the genotypic evaluation of twelve groups of Piel del Sapo melon hybrids in the Rio Grande do Norte State. Studies on adaptability and stability of the predicted genotypic values were performed by MHPRVG procedure (current Harmonica Relative performance of Genetic Values). The traits evaluated were yield and soluble solids. It was genotype x environment interaction for both variables in all groups of hybrids. There was a predominance of complex part of the interaction for the two traits evaluated. The method of harmonic mean relative performance of genotypic values (MHPRVG), based on genotypic values predicted by mixed model, allows the identification of Piel del Sapo melon hybrids with stability adaptability. The experimental hybrid HP-09 is more promising for cultivation at Mossoró-Assu pole because it presents high stability, adaptability and productivity
Genotypic x environment interaction, adaptability and stability of pele de sapo melon hybrids by mixed model
Keywords: Cucumis melo; BLUP; MHPRVG; Produtividade; Sólidos solúveis; Cucumis melo; BLUP; MHPRVG; Productivity; Soluble solids; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA